An assessment of burden associated with problem joints in children and adults with moderate or severe haemophilia A: analysis of the CHESS-Paediatrics and CHESS II cross-sectional studies - Paul McLaughlin; Hortensia De la Corte-Rodriguez; Tom Burke; Francis Nissen; Martynas Aizenas; Katya Moreno; Jamie O’Hara (Orphanet Journal of Rare Diseases)
Abstract Background Clinical research has offered many definitions and fragmented perspectives of joint morbidity in haemophilia. As joint damage, pain and mobility impairment can be present without clinical record of persistent bleeding, a person-centric joint morbidity characterisation remained a priority for the haemophilia community, giving rise to the ‘problem joint’ concept. As diagnosing and managing joint morbidity is critical, the aim of this study was to analyse the holistic burden of problem joints in people with moderate or severe haemophilia A (HA). Data from the ‘Cost of Haemophilia in Europe: a Socioeconomic Survey’ (CHESS) cross-sectional studies were used. CHESS-Paediatrics included male paediatric patients (≤ 17 years) with congenital moderate or severe haemophilia, while CHESS II included adult males (≥ 18 years) of any severity. Both studies sought to collect detailed information on the clinical, economic and humanistic burden of haemophilia. Demographics, clinical outcomes, treatment regimen, adherence, physical activity, healthcare resource use and number of problem joints were evaluated and described by HA severity and number of problem joints (none, 1, ≥ 2). Results In total, 1171 people with non-inhibitor moderate or severe HA from CHESS-Paediatrics (n = 703) and CHESS II (n = 468) were included in this analysis. Presence of problem joints was more prevalent among CHESS II participants (44%) than in CHESS-Paediatrics (14%). Around two-thirds (67%) of CHESS-Paediatrics and 39% of CHESS II participants received prophylactic factor VIII replacement therapy. The presence of chronic pain was greater in severe HA with ‘ ≥ 2’ problem joints in both cohorts. Clinical symptoms and bleed-related hospitalizations were more prevalent in the presence of problem joints regardless of HA severity in both cohorts. Conclusions This analysis of the CHESS population studies has expanded on previous work by examining the relevance of the problem joint measure of haemophilic morbidity and its associated burden. Adverse clinical symptoms and increased bleed-related hospitalizations were observed in the presence of problem joints in both children/adolescents and adults across HA severities. Use of person-centric characterizations of joint morbidity may improve analysis of long-term outcomes and lead to improvements in future haemophilia care.